Coping techniques to reduce Burnout Syndrome - Gómez Uriarte, Miriam Alexandra (2020)
In the company Imperios Operadores Logísticos S.A, a questionnaire of Burnout Syndrome was applied to 28 participating collaborators, whose diagnosis showed that 39% was in the middle level and 61% in the high level of the syndrome; signs that these employees were emotionally tired, unmotivated and indifferent to their coworkers. Contrary case happened in the subsequent test, whose results managed, that no collaborator has a high level of Burnout Syndrome; otherwise 25% of those evaluated managed to have a low level, while 75% were located at a medium level, for this reason the application of the coping techniques developed with said collaborators managed to decrease the high levels of Burnout Syndrome. To the effect, it is affirmed that the cognitive restructuring techniques, situation management and problem solving technique proposed by Majoney and Arnkoff (1978), allowed to reduce said syndrome, these dimensions proposed by Maslach and Jackson (1981b) were emotional exhaustion where of 14% located in the low level improved significantly to 75%, while the depersonalization dimension of 64% located in the low level, achieved of 86%, with respect to the personal achievement dimension of a high level of 0%, increased to 68 %. Finally, it is concluded that the applied coping techniques were effective reaching a significance level of p_value = 0.001 <0.05, affirming that the techniques managed to decrease Burnout Syndrome.